Pengaruh konsentrasi starter dan macam buah terhadap karakteristik kefir air - Tri Kurniawidi; Deny Utomo (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Water kefir is a probiotic drink as a result of fermentation by lactobacillus acid bacteria, acetobacter and yeast. Fruits and other ingredients could be added to obtain water kefir with specific flavor and aroma. This research aims to observe the effect of starter concentration and kind of fruit used on the characteristics of water kefir, and to determine the best combination preferred by the panelists. This study used two factorial randomized design with three repetitions. The factors used are the starter concentration (5 %, 8 %, and 11 %) and the kind of fruit used (snake fruit, pineapple, and papaya). Results showed that different starter concentration had an effect on brix, pH, alcohol content and density of water kefir, while different kinds of fruit had an effect on brix. Based on organoleptic test the most preferred water kefir is pineapple water kefir with 8 % starter concentration.